Anticoagulant Prevention in Patients with Atrial Fibrillation: Alternatives to Vitamin K Antagonists - Kozlowski, Dariusz; Budrejko, Szymon; Raczak, Grzegorz; Rysz, Jacek; Banach, Maciej (Current Pharmaceutical Design, 2013)
Patients with nonvalvular atrial fibrillation (AF) and risk factors for stroke need anticoagulation to avoid thromboembolic complications. Vitamin K antagonists (VKAs) are an established pharmacological group the use of which is recommended by guidelines. However, VKAs (like warfarin) have major disadvantages, such as a variable dose-effect relationship, drug and food interactions, the need for regular blood testing and dose titration, and, finally, a substantial risk of bleeding. New oral anticoagulants are intended to replace warfarin, being at least as safe and effective, and lacking some of the disadvantages of VKAs. Clinical data for dabigatran, rivaroxaban, apixaban and edoxaban, and other new drugs, are discussed in this article with special focus on their use in nonvalvular AF.
Keywords: ximelagatran